JURIDICAL REVIEW OF CONSUMER PROTECTION IN BUYING AND SELLING TRANSACTIONS USING ELECTRONIC MEDIA - I Kadek Krisnandika Aristya Putra; I Nyoman Bagiastra (Transpublika Publisher, 2024)
With the advanced digital technology, there are a lot of changes in how people interact and do businesses. E-commerce growth has been stimulated by the rise of internet usage and electronic systems in Indonesia. This change, propelled by development in information technology, has enabled trading to take place through online platforms instead of face-to-face meetings. The purpose of this study is to look at consumer legal protection within e-commerce transactions in Indonesia. The research employs a normative legal approach which explores laws regulating e-commerce such as Law Number 8 of 1999 regarding consumer protection and its amendment. It was established that although there is a comprehensive legal framework for consumer protection; however, some of the challenges include lack of consistency in law enforcement as well as inadequate consumers education among others making it hard to improve consumers’ right at the time when everything is becoming digital.